PESANTREN AND THE TRANSMISSION OF SANAD AL-QUR’AN: TRACKING SANAD TAHFIZ CONNECTIONS IN INDONESIA - Ayatin L.N, Febriana; Fadlillah, Fadlillah (Universitas Nurul Jadid, 2023)
This research aims to trace the connection between the sanad of the Qur’an at the Pesantren Nurul Islam (Nuris) Jember, which has recently developed along with the spread of the Qur’an and tahfiz institutions in Pondok Pesantren, especially modern pesantren, where sanad is lacking get attention. Therefore, dissecting a scientific network and, more specifically, the path of sanad qira’at in studying the Qur’an is critical. This research is field research which is presented descriptively. The collected data will be analyzed using a descriptive approach to determine the connection between the sanad tahfiz at the Pesantren Nuris. This research finally resulted in a conclusion that; 1) the sanad of the Qur’an at the Pesantren Nuris Jember, taking the sanad from the caretaker, Gus Rabith Qashidi, which was obtained from his teacher in Egypt, Shaikh Asyraf Hamid Hisanain Muhammad, who is connected to the Prophet Muhammad, 2) the method of giving the sanad of the Qur’an in Nuris Jember is included in the ardhan faqath method where a student reads to his teacher until complete without having to listen to the teacher’s reading first, and 3) the sanad category owned by Gus Rabith Qashidi is included in the category of new sanad routes that have reached Indonesia, in the sense that path obtained by Indonesian ulama from the results of scientific pursuits in the Middle East.